Persuading the divine: on the composition of Hittite Prayers - Peut, Lidewij E. van de (Studien zu den Boğazköy-Texten, 2022)
Cover -- Title Pages -- Contents -- Illustrations -- Figure 1. Textual history of the introduction proper with instruction -- Figure 2. Textual history of the hymns in CTH 376.II and CTH 377 -- Figure 3. Relationships between Plea II of CTH 376.II and related pleas -- Figure 4. Relationships between passages with wishes to reveal a past offence -- Figure 5. Textual history of KUB 24.3+ iii 12′-17′ and CTH 377 50′-51′ -- Figure 6. Textual history of CTH 376.I, CTH 376.III, CTH 376.II, and CTH 377 -- Figure 7. Relationships between CTH 372, CTH 373, and CTH 374 -- Figure 8. Lower part of the obverse KUB 24.4+ with ruling and Randleiste -- Figure 9. Beginning of the paragraph lines after KUB 24.4+ rev. 13, 15, 17 -- Figure 10. Wedge head within the ruling after VBoT obv. 3‴ -- Figure 11. Part of the ruling after VBoT 121 obv. 11‴ -- Figure 12. End of KUB 24.3+ i 28′ -- Figure 13. Part of the intercolumnium of KUB 24.3+ obverse -- Figure 14. Beginning horizontal ruling after KUB 24.3+ ii 55 -- Figure 15. Beginning horizontal ruling after KUB 24.3+ ii 60 -- Figure 16. End of the horizontal ruling after KUB 24.3+ ii 44 -- Figure 17. Double ruling after KUB 24.1+ iv 18, preceding the colophon -- Figure 18. Part of the ruling after KUB 24.1+ iii 15′ -- Figure 19. Part ruling after KUB 24.1+ i 17 -- Figure 20. KUB 24.2 reverse, lower end -- Figure 21. Selected attestations of AḪ -- Figure 22. Selected attestations of ḪAR -- Figure 23. Selected attestations of AG -- Figure 24. Selected attestations of AL -- Figure 25. Selected attestations of AR -- Figure 26. Selected attestations of AZ -- Figure 27. Selected attestations of UG -- Figure 28. Selected attestations of BI -- Figure 29. Selected attestations of DA -- Figure 30. Selected attestations of ID -- Figure 31. All attestations of DI -- Figure 32. Selected attestations of KI.